2018
DOI: 10.1038/s41598-018-29685-z
|View full text |Cite
|
Sign up to set email alerts
|

Targeting protein-protein interactions for therapeutic discovery via FRET-based high-throughput screening in living cells

Abstract: We have developed a structure-based high-throughput screening (HTS) method, using time-resolved fluorescence resonance energy transfer (TR-FRET) that is sensitive to protein-protein interactions in living cells. The membrane protein complex between the cardiac sarcoplasmic reticulum Ca-ATPase (SERCA2a) and phospholamban (PLB), its Ca-dependent regulator, is a validated therapeutic target for reversing cardiac contractile dysfunction caused by aberrant calcium handling. However, efforts to develop compounds wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(75 citation statements)
references
References 71 publications
4
71
0
Order By: Relevance
“…28 We varied the ratio between the donor molecule (GFP-SERCA2a) and acceptor molecule (RFP-PLBWT), and found that the maximal energy transfer efficiency E (fractional decrease of the fluorescence lifetime) in this live-cell based system saturates at 0.10, as previously reported. 28 We transfected cells expressing GFP-SERCA2a and RFP-PLBWT with either untagged PLBWT or PLBM containing TM mutations (L31A, I40A, or L31A/I40A). Displacement of the RFP-PLBWT from its interaction with GFP-SERCA2a was observed as a decrease in the FRET efficiency relative to that measured in control cells expressing only the GFP-SERCA/RFP-PLBWT donor-acceptor pair (Fig.…”
Section: Fret Assay Demonstrates Serca-binding Competition Between Plsupporting
confidence: 56%
See 4 more Smart Citations
“…28 We varied the ratio between the donor molecule (GFP-SERCA2a) and acceptor molecule (RFP-PLBWT), and found that the maximal energy transfer efficiency E (fractional decrease of the fluorescence lifetime) in this live-cell based system saturates at 0.10, as previously reported. 28 We transfected cells expressing GFP-SERCA2a and RFP-PLBWT with either untagged PLBWT or PLBM containing TM mutations (L31A, I40A, or L31A/I40A). Displacement of the RFP-PLBWT from its interaction with GFP-SERCA2a was observed as a decrease in the FRET efficiency relative to that measured in control cells expressing only the GFP-SERCA/RFP-PLBWT donor-acceptor pair (Fig.…”
Section: Fret Assay Demonstrates Serca-binding Competition Between Plsupporting
confidence: 56%
“…5 We demonstrated previously that the interaction between the cardiac Ca 2+ pump, SERCA2a, and its principal inhibitor, PLB, can be measured via FRET in HEK293 cells. 28 In the present study, we applied this FRET assay to measure the competition of non-inhibitory PLBM and RFP-labeled PLBWT for binding to GFP-SERCA2a. We used this assay to measure the relative affinity of non-inhibitory PLBM and identified a double mutant (L31A/I40A) that binds with affinity greater than PLBWT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations